APLIKASI COCOPEAT SEBAGAI MEDIA SEMAI JELUTUNG ( Dyera lowii Hook. f ) COCOPEAT APPLICATION AS SEEDLING MEDIA OF Dyera lowii Hook.f - Zikri Al Fikri; M. Mardhiansyah; Viny Volcherina Darlis (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Peatland is the result of the accumulation of organic matter from weathering vegetation. Peat restoration is a process to restore the ecological function of peat areas. The efforts to restore peat are carried out through three approaches, one of peat restoration is regrowth. Dyera lowii Hook.f is one types of local plants of double yield peat bog forest namely sap and wood with high economy. The purpose of this research is to determine the best application of the cocopeat composition as plant media to the growth of Dyera lowii. The study used a Completely Randomized Design (CRD) method consisting of 5 treatments and 4 replications so that 20 units of the experiment would be obtained. The treatments are: C1 (without application of cocopeat/ control) C2 (application of cocopeat 25%-75% peat soil) C3 (application of cocopeat 50%-50% peat soil) C4 (application of cocopeat 75%-25% peat soil) C5 (application of cocopeat 100%). The data obtained from the research results were analyzed with variance using SPSS 20.0. furthermore if the results of the variance have a significant effect, further analysis will be carried out using the (DNMRT) at the 5% level. The best application of the composition as plant media, namely cocopeat 75% and 25% peat soil in general showed the best result increase in seedling height of 1,16 cm, increase in seedling diameter of 1,23 mm, and top root ratio of 1,91. Keywords: Cocopeat, Dyera lowii Hook. f, seedling media